APPENDIX: Oxidation and Dissolution of Refractory Gold Concentrate in Alkaline Hypochlorite Solutions - Regidor, Hanna Czarise; Mendoza, Herman; Mena, Manolo (Philippine Engineering Journal; Vol 43 No 2 (2022), 2022)
Appendix: Oxidation and Dissolution of Refractory Gold Concentrate in Alkaline Hypochlorite Solutions